The Implementation of Discipline Character Education Values in Elementary School Students - Kintani, Nenden; Maftuh, Bunyamin (International Conference on Elementary Education, 2024)
This research aims to describe the implementation of disciplined character education values in elementary schools and is expected to find policies that support the success of character education. The approach to this research uses a qualitative approach. This research was conducted at SDN 049 DM, with the subjects being the principal, teachers and students. Data was collected through observation, interviews and documentation. The data validity checking technique used is the triangulation technique. The results of the research show that in implementing disciplined character education at SDN 049 DM through seven policies, namely (1) creating a character education program, (2) establishing school rules and class rules, (3) carrying out Dhuha prayers and Dhuhur prayers in congregation, (4 ) making affective posts in each class, (5) integrating student disciplinary behavior at home through daily activity monitoring books, (6) involving parents (7) involving the school committee.